KOMPARASI KEBIJAKAN PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN DESA WISATA EKOLOGIS STUDI KASUS : DESA TENGANAN DAN DESA SUANA - Wirantari, I Dewa Ayu Putri (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
.The Bali Provincial Government carries out special interest tourism development, namely in the form of a tourism village development program which is used as a reference in managing ecological tourism villages created for and by the community, and the profits obtained will be put back into the community and for the conservation of the villages. The concept of an Ecological Tourism Village can restore the essence of a community-based tourism business model. Ecological Tourism Villages have the benefit of creating tourism development models, especially tourist villages whose communities can preserve their natural and socio-cultural potential based on local wisdom, and are able to support the finances of traditional villages in developing villages that are independent and able to manage village finances through the Village Ecotourism Network. The village government has the right to prepare village development plans in accordance with the authority referred to in village development planning. Ecological tourism villages in an effort to alleviate poverty in Suana Village and Tenganan Pegringsingan Village have three stages, namely the awareness stage, communication links and training as an effort to empower the community by maximizing all the potential that exists in the Ecological Tourism Village. The research method used is descriptive qualitative research using snowball sampling